The role of repeat computerized cranial tomography in pediatric blunt head trauma - Sertaç Güler; Dilber Üçöz Kocaşaban; Yahya Kemal Günaydın (National Scientific Medical Center, 2023)
Introduction: Computed cranial tomography (CCT) is commonly used in emergency departments (EDs) for pediatric blunt head injury (BHI) management. Cranial tomography is also repeated often unnecessarily due to physicians' concerns about detecting the early onset of a possible new injury or progression of an existing one. This study aims to evaluate whether routine RCCT provides a significant change in patient management. Material and methods: The study was performed as a 2-year retrospective analysis in the ED of a tertiary hospital. The medical records of pediatric BHI patients were reviewed, and the study included accessed data of 104 patients who underwent at least two CCT during their stay in the ED. Results: The study included 104 out of 533 BHI patients. The mean age of these 104 patients was 6.2 years (median=4.5 years), and the majority were male (n=82, 78.9%). When the initial CCT results of the patients were analyzed, it was found that 51% (n=53) of the tomography results were normal. While there were substantial changes in 7 of the RCCTs, there were no significant changes in 97. Only 4 of these 7 patients who had significant changes were taken to the emergent operating room. None of these patients belonged to the group of patients whose CCT was classified as "normal" on admission (p<0.05). Conclusion: According to our results, routine RCCT for BHI in pediatric patients did not result in a significant change in patient management.